The comparison of Ibn Arabi’s Mohammadan reality with Filon’s Logos - reza gandomi nasrabadi (حکمت اسرا, 2014)
There have been numerous discussions over the sources of Ibn Arabi’s inspiration. One of the thinkers who has been named as an inspiration source for Ibn Arabi is Filon Eskandarani. With an emphasis on Filon’s Logos and Ibn Arabi’s Mohammadan reality, this article seeks to identify the similarities and differences between these two concepts. However, it is not intended to confirm that if Ibn Arabi had been influenced by Filon in the mentioned dimensions, since it is impossible to confirm or reject this. Both thinkers have provided descriptions and functions about Logos and Mohammadan reality that initially seem to be alike. Logos and Mohammadan reality can be viewed through three dimensions of ontology, epistemology, and function or value. From the ontological viewpoint, the relationship between the two foregoing concepts with God, universe, and mankind is examined. From epistemological stance, the role of the two concepts in identifying mankind and revelation is scrutinized. Finally, from the value or function standpoint, this question is answered that with acceptance of Logos and Mohammadan reality, what problems can be solved.